The representation of social actors in the tweets of Jair Messias Bolsonaro - Fadanelli (UCS), Sabrina Bonqueves (2020)
Discourses via social networks have been widely used by politicians, who often apply ideological bias in different ways depending on their interests. Therefore, this study aims to analyze the Representation of Social Actors (Fairclough 2003) in the speech of Jair Messias Bolsonaro, and to verify if changes in these representations occur in the periods before and after being elected. The current Brazilian president's tweets are used as corpora, the first one comprising of 111 tweets published on Bolsonaro's official Twitter, between October 8 to 27, 2018, the pre-campaign period for the second round of Brazilian elections. The second one comprises 83 tweets, from August 8 to 27, 2019, a period in which the candidate already held the position of President of the Republic. The theoretical contribution consists mainly of Fairclough studies within Critical Discourse Analysis, complemented by Foucault (2012) and Charaudeau (2010). Results point to changes in the president's speech in most of the analyzed occurrences.